Recovery of gut microbiota of healthy adults following antibiotic exposure - Palleja, Albert; Bork, Peer (Nature microbiology, 2018)
Here the authors show that the human gut microbiome can recover after a clinically relevant, broad-spectrum antibiotic treatment and characterization of the resistome indicates that antibiotic resistance genes can impact the recovery process.
Gesehen am 16.04.2020